Medicinal Plants of Sham Valley in Trans-Himalayan region of Ladakh, India - Jigmet Namgial; S.K. Gupta; Sonam Dawa (Annals of Arid Zone, 2025)
The identification and documentation of medicinal plants is essential for preserving knowledge of traditional medicinal system, particularly in ecologically unique and culturally rich regions like Ladakh. An exploratory survey was carried out in Sham valley of district Leh, union territory of Ladakh, India in 2019 and 2020 aimed at collection and presentation of information regarding valuable medicinal and herbal wealth and its use in traditional “Amchi” system of Ladakh. A total of 61 medicinal plant species were documented, comprising 1 tree, 3 shrubs, and 57 herbs, distributed across 52 genera and 31 families. These plants are widely used in traditional medicine to treat a range of ailments, with notable applications for cough, fever, rheumatism, headache, diarrhoea, kidney disorders, and heart diseases.